From Text to Praxis: A Philosophical Examination of Qur’anic Values in Constructing Ethical Consciousness within Modern Educational Institutions - Muhamad Muhamad; Shifany Maulida Hijjah (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
This study explores the integration of Qur'anic ethical values in modern educational settings, focusing on how philosophical hermeneutics, combined with reflective pedagogy, can enhance students' ethical consciousness. The Qur'an, with its emphasis on key ethical principles such as justice (adl), compassion (rahmah), and responsibility (amanah), provides a foundational framework for cultivating moral behavior in students. The study highlights the potential of reflective pedagogy to contextualize these ethical teachings, ensuring they remain relevant to contemporary issues. The findings suggest that when Qur'anic values are approached through an interpretative and dialogical lens, they can be effectively internalized by students, promoting not only theoretical knowledge but also practical ethical behavior. This study also examines the challenges of integrating religiously oriented ethical frameworks in secular educational systems and the complexities of making Qur'anic teachings resonate with diverse student populations. The implications for educational practice are significant, suggesting that the incorporation of Qur'anic values can bridge the gap between religious teachings and moral actions, fostering a more ethically aware and responsible student body. The research concludes with recommendations for further exploration into the practical implementation of this approach in varied educational contexts, especially in multicultural and multi-faith settings, and highlights the need for long-term studies to assess the impact on students' ethical development.